Okorusu tailings – Part II: REE mineralisation, and oxygen and carbon isotope variations - Lohmeier, S.; Machleidt, Jakob; Klemd, Reiner; Ellmies, R. (South African Journal of Geology, 2023)
The Okorusu carbonatite complex and the mine’s tailings dump constitute a potential resource of rare earth elements meaning lanthanides and yttrium (REY). Small (≤100 μm), hydrothermal REE fluorcarbonates (bastnäsite, parisite, röntgenite and synchysite) are the principal light REE carriers while the heavy REE and Y are primarily hosted in magmatic apatite, magmatic-hydrothermal carbonates (calcite, dolomite, ankerite) and hydrothermal fluorite. Bastnäsite and röntgenite occur as individual, liberated crystals in the tailings albeit syntaxial intergrowths of acicular parisite-synchysite-röntgenite are more common. There is a clear trend of decreasing REY contents in the magmatic carbonates over the early hydrothermal carbonates to the late hydrothermal carbonates. The lower total REY abundance in the hydrothermal carbonates is interpreted to be mainly a consequence of their limited redistribution during hydrothermal activity following the breakdown of the primary magmatic minerals and precipitation of REE fluorcarbonates. During this process hydrothermal fluids changed the isotopic composition of the Okorusu carbonatites by shifting δ13C-δ18O pairs of magmatic carbonatite (δ13C:-6.5‰ to-5.4‰; δ18O: +6.4‰ to +11.2‰) to higher values of hydrothermally modified carbonatite (δ13C:-4.2 to-2.2; δ18O: +12.0‰ to +17.5‰). The preferential presence of REY in the magmatic carbonates and to a minor degree in the hydrothermal carbonates in the Okorusu carbonatite and tailings is an important exploration tool for primary magmatic REY mineralisations. The recovery of REE fluorcarbonates can be considered in the development of the flowsheet for the planned recycling of the tailings material as a potential REY by-product.
CRIS-Team Scopus Importer:2023-11-03